The relationship between involvement, destination emotions and place attachment in the Porto wine cellars - Santos, Vasco (My University, 2017)
Purpose – This paper aims to measure the role of involvement, destination emotions and place attachment in the behavioural intentions of wine tourists when visiting Porto wine cellars. Design/methodology/approach – An interceptive survey was conducted with wine tourists during their visits to four Porto wine cellars. A convenience sample of 918 international visitors was obtained. A structural equation model using partial least squares analysis was used to test the hypothesis and the validity of the constructs and model. Findings – The structural model results indicated that wine tourists’ personal involvement and their wine involvement have a significant and direct influence on destination emotions and place attachment in Porto wine cellars during the visits, which determines their future behavioural intentions. Research limitations/implications – The generalizability of the results may be limited owing to the sample and the data collection method and the short time frame of the data gathering. Practical implications – There is a growing potential for researchers and managers to achieve benefits from the proposed model that will support the efforts for wine tourism theory and practice, such as brand positioning strategies and formulation of sharper marketing strategies. Originality/value – This is the first study to demonstrate the combined use of personal and wine involvement on destination emotions along with place attachment in a wine tourist behaviour context. This approach extends the scope into a wine tourism context because the combination of these three constructs has never been held in the area of wine tourism destinations.
Keywords: Marketing; Consumer behaviour; Tourism; Structural equation models; Scale development/testing